The golden years of advertising the roaring nineties of separating people from their money - Vaske, Hermann; Trott, David ([Germany : Hermann Vaske Group IE], 2005)
This DVD highlights Vaske's documentaries over the past decade, featuring Dennis Hopper taking you on a journey through the'Golden Years'. Containing interviews about various facets of creativity with a global who?s who including the Dalai Lama, musicians Bono and David Bowie, filmmakers Roman Polanski and David Lynch, advertisers Frank Lowe and John Hegarty, politicians Mikhail Gorbachev and Vaclav Havel and many others
The fine art of separating people from their money -- The A-Z of separating people from their money --The Ten commandments of separating people from their money
Title from container
Special features: Scene selection, making of and trailers
DVD format
Keywords: Advertising; Creative ability